Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian pada Kosmetik Wardah di Toko Kosmetik Arab Desa Cisarua Kabupaten Sukabumi - Rusfikasari, Silvi; Fitralisma, Gian; Sulaiman, Eman (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The formulation of the research problem aims to assess whether there is an influence of brand image and product quality on purchasing decisions at Arab cosmetic stores in Cisarua Village, Sukabumi Regency. The results of this study indicate that partially brand image has a positive and significant effect on the decision to purchase Wardah cosmetics at an Arabic cosmetic store in Cisarua Village, Sukabumi Regency with a t-test result of (3.466> 1.99085) and a sig value (0.001 <0.05), product quality has a positive and significant effect on the decision to purchase Wardah cosmetics at an Arabic cosmetic store in Cisarua Village, Sukabumi Regency with a t-test result of (6.574> 1.99085) and a sig value (0.000 <0.05). Based on the results of the F-test, it produces F_count> from F_table (82.572> 3.115) and the magnitude of sig 0.000 <0.05 so it can be concluded that simultaneously there is a positive and significant influence between the brand image variable and product quality on purchasing decisions. Based on the results of the R square determination coefficient test, it partially shows that the influence of the brand image variable is 50.4% and the influence of the product quality variable is 63.2%. The results of the determination coefficient test of the adjusted R-square value showed a result of 0.674, which means that 67.4% of the decision to purchase Wardah products at the Arab cosmetic shop in Cisarua Village, Sukabumi Regency was influenced by the brand image and product quality variables, while the remaining 32.6% was influenced by other variables that were not studied.